PENERAPAN PROGRAM ISO 9001:2015 DAN CARA DISTRIBUSI ALAT KESEHATAN YANG BAIK (CDAKB) UNTUK MENUNJANG KEGIATAN USAHA DI PT. MITRA BAHAGIA CITRA MEDIKA SURABAYA - Nurany, Fierda; Ismail, Ismail (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2024)
This study aims to analyze the application of the ISO 9001:2015 and CDAKB programs, analyze the factors that influence the ISO 9001:2015 and CDAKB programs, and analyze the efforts made by PT Mitra Bahagia Citra Medika Surabaya in maintaining the quality of the quality management system according to the ISO 9001:2015 and CDAKB programs. The research method used is a type of qualitative research. The informants in this study were employees of PT Mitra Bahagia Citra Medika Surabaya. Data collection techniques in this study were interviews and documentation. The data analysis technique used in this study is interactive model analysis. The results of this study indicate that: (1) Implementation of the ISO 9001:2015 Program and Good Methods for Distribution of Medical Devices (CDAKB) at PT Mitra Bahagia Citra Medika has gone well according to the clauses required; (2) Internal constraints on program implementation of ISO 9001:2015 and Good Medical Device Distribution Methods (CDAKB): there are very few obstacles that occur; and (3) External constraints on the implementation of the ISO 9001:2015 program and Good Medical Device Distribution Methods (CDAKB), namely the storage area of goods that are still not wide enough